Application of Tsukamoto's Fuzzy Logic in Determining the Level of Service Quality at the Bengkulu Province Library and Archives Service - Wiwin Purnama Sari; Mesterjon Mesterjon; Arius Satoni Kurniawansyah (Jurnal Komputer, Informasi dan Teknologi, 2021)
Fuzzy logic is part of an artificial intelligence system that emulates human ability to think into algorithms which are then run by machines. At the Bengkulu Province Library and Archives Service, there is no application that can help to determine the quality of service based on the value given by the respondent. Service Quality Level Application at the Bengkulu Provincial Library and Archives Service is an application built to facilitate library members in providing value to the quality of services provided by the Bengkulu Provincial Library and Archives Service, and this application applies the Tsukamoto Fuzzy Logic method where the level of service quality is divided into 5 levels, namely Very Good, Good, Fairly Good, Less Good and Not Good. Based on the results of the tests that have been carried out, the functionality of the application has run as expected, and the Service Quality Level Application at the Bengkulu Provincial Library and Archives Service for 2021 is Very Good and this application is able to display the level of service quality every year through the Tsukamoto Fuzzy Logic Method approach.